Re-mapping the iconic Okonkwo of ‘Things Fall Apart’ through a fichtean map of self-exploration, self-consciousness and self-awareness - Farivar, Marziyeh (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper aims at placing the ‘Things Fall Apart’, a microcosm of African life, onto the Fichtean map of self-exploration, self-consciousness and self-awareness. Chinua Achebe (1930-2013), the leading figure of African anti-colonial literature, constructed his protagonist, Okonkwo, and presented his transformation in the novel from the pre-colonial time to the post-colonial days in Umuofia. Okonkwo’s characterisation in terms of his association with his family, relations, religion, and power inclinations, mirrors his identity and tendencies as a self-sufficient independent character. However, as the situation changes, apart from the colonial terrain, his ‘I’ is challenged and, consequently, his whole world turned upside-down and crumbled. Observing Okonkwo through Fichtean theory of subjectivity provides a philosophical perspective to show his search for ‘I’ despite all the changes which had been taking place in his surroundings. The experiences that he had been going through brought about a new ‘I’ which was different from his former sense of individuality and subjectivity. Fichte (1762-1814) brought the ‘I’ into a new light of having an active positioning, meaning that the ‘I’ lacks the capability of exploring itself and achieving self-awareness and consciousness in a solitary life. The choice of being independent does not mean subjectivity since, in that condition, the senses of recognition and perception cannot be fulfilled. What is significant is that such senses may not be considered as the metaphysical phenomena; but they are structurally epistemological. Okonkwo’s journey of self-exploration leading to his self-consciousness and self-awareness is demonstrated to be related to the outside world.